Immunity against Non-Melanoma Skin Cancer and the Effect of Immunosuppressive Medication on Non-Melanoma Skin Cancer Risk in Solid Organ Transplant Recipients - Dixie Bakker; Walbert J. Bakker; Marcel W. Bekkenk; Rosalie M. Luiten (Cells, 2023)
Non-melanoma skin cancers (NMSCs) occur frequently in the Caucasian population and are considered a burden for health care. Risk factors include ultraviolet (UV) radiation, ethnicity and immunosuppression. The incidence of NMSC is significantly higher in solid organ transplant recipients (SOTRs) than in immunocompetent individuals, due to immunosuppressive medication use by SOTRs. While the immunosuppressive agents, calcineurin inhibitors and purine analogues increase the incidence of NMSC in transplant recipients, mTOR inhibitors do not. This is most likely due to the different immunological pathways that are inhibited by each class of drug. This review will focus on what is currently known about the immune response against cutaneous squamous cell carcinoma (cSCC) and basal cell carcinoma (BCC), two of the main types of NMSC. Furthermore, we will describe the different classes of immunosuppressants given to SOTRs, which part of the immune system they target and how they can contribute to NMSC development. The risk of developing NMSC in SOTRs is the result of a combination of inhibiting immunological pathways involved in immunosurveillance against NMSC and the direct (pro/anti) tumor effects of immunosuppressants.